Can Surgical Technique Affect the Success of Endoscopic Treatment in Children with Vesicoureteral Reflux and Overactive Bladder Syndrome? - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TİNAY, İLKER; TARCAN, TUFAN; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2015)
Objective Traditional subureteral transurethral injection (STING) and Double hydrodistention-implantation (Double-HIT) injection techniques for vesicoureteral reflux (VUR) treatment are a less invasive, yet very effective options. The influence of injection techniques in treatment success is not adequately searched in children with overactive bladder syndrome (OAB). The objective of this study to compare the short-term success rates of STING and Double-HIT techniques in children with OAB-VUR complex. Materials and Methods Children who underwent endoscopic injection for VUR between 2010 and 2013 were retrospectively evaluated. Patients were grouped into two groups according to the surgical techniques (STING or Double-HIT). Success of the treatment was defined with a negative voiding cystourethrogram at the 6th postoperative week. Patients were evaluated according to sex, age, pre- and postoperative reflux grades, laterality, type and volume of bulking agent and presence of OAB. Results Both groups were similar in terms of sex, age, lower urinary tract dysfunction, reflux grade and success rates. Surgical technique, score of pediatric lower urinary tract symptom questionnaire, age, sex, laterality of reflux and type of the bulking agent found to have no effect on the overall success rates (p>0.05). Presence of OAB and/or a high grade reflux were identified as statistically significant predictive factors that could affect the treatment results. Conclusion The short-term surgical success of the double-HIT and STING techniques showed no difference in children with OAB. The presence of a high grade reflux and/or OAB seemed to be the main factors for overall success in endoscopic VUR surgery.
Keywords: Pediatrics; vesicoureteral reflux; overactive bladder; endoscopic surgery; surgery; therapy